The Association Between Physical Activity and The Development of Degenerative Spine Disease: A Review - Chodkowski, Jakub; Korotko, Urszula (Quality in Sport, 2025)
Introduction: Degenerative spine disease (DSD) encompasses conditions such as intervertebral disc degeneration, spinal stenosis, and spondylosis, often linked to aging and lifestyle factors. Physical activity is frequently proposed as a modifiable factor influencing the onset and progression of DSD. This review explores the relationship between physical activity and DSD development, highlighting its potential role in prevention and management. Materials and Methods: A comprehensive literature review was conducted using PubMed, Scopus, and Web of Science databases, focusing on studies published between 2000 and 2024. Keywords included "degenerative spine disease," "physical activity," "exercise," and "spinal health." Inclusion criteria comprised observational studies, clinical trials, and meta-analyses that examined physical activity’s effects on DSD risk or progression. Results: Findings suggest a dual role of physical activity in DSD development. Moderate, consistent exercise, particularly low-impact activities like swimming, yoga, and walking, appears protective, enhancing spinal muscle strength, flexibility, and disc nutrition. Conversely, high-intensity or repetitive loading activities, such as heavy lifting or contact sports, are associated with an elevated risk of accelerated degeneration. Evidence highlights a dose-dependent relationship, where activity type, intensity, and duration critically modulate outcomes. Limited studies suggest potential genetic and biomechanical factors influencing individual responses to physical activity. Conclusions: Physical activity exerts a complex influence on DSD development, with moderate exercise showing potential benefits while excessive strain may increase risks. Tailored exercise regimens could mitigate DSD progression, emphasizing the importance of personalized physical activity guidelines. Further longitudinal studies are needed to clarify mechanisms and optimize prevention strategies.